Health Care Professionals' Experiences of Patient-Professional Communication Over Patient Portals: Systematic Review of Qualitative Studies - Laukka, Elina; Huhtakangas, Moona; Heponiemi, Tarja; Kujala, Sari; Kaihlanen, Anu-Marja; Gluschkoff, Kia; Kanste, Outi (JMIR Publications, 2020)
BackgroundThe popularity of web-based patient-professional communication over patient portals is constantly increasing. Good patient-professional communication is a prerequisite for high-quality care and patient centeredness. Understanding health care professionals' experiences of web-based patient-professional communication is important as they play a key role in engaging patients to use portals. More information is needed on how patient-professional communication could be supported by patient portals in health care. ObjectiveThis systematic review of qualitative studies aims to identify how health care professionals experience web-based patient-professional communication over the patient portals. MethodsAbstract and full-text reviews were conducted by 2 reviewers independently. A total of 4 databases were used for the study: CINAHL (EBSCO), ProQuest (ABI/INFORM), Scopus, and PubMed. The inclusion criteria for the reviewed studies were as follows: the examination of health care professionals' experiences, reciprocal communication between patients and health care professionals, peer-reviewed scientific articles, and studies published between 2010 and 2019. The Joanna Briggs Institute's quality assessment criteria were used in the review process. A total of 13 included studies were analyzed using a thematic synthesis, which was conducted by 3 reviewers. ResultsA total of 6 analytical themes concerning health care professionals' experiences of web-based patient-professional communication were identified. The themes were related to health care professionals' work, change in communication over patient portals, patients' use of patient portals, the suitability of patient portals for communication, the convenience of patient portals for communication, and change in roles. ConclusionsHealth care professionals' experiences contain both positive and negative insights into web-based patient-professional communication over patient portals. Most commonly, the positive experiences seem to be related to the patients and patient outcomes, such as having better patient engagement. Health care professionals also have negative experiences, for example, web-based patient-professional communication sometimes has deficiencies and has a negative impact on their workload. These negative experiences may be explained by the poor functionality of the patient portals and insufficient training and resources. To reduce health care professionals' negative experiences of web-based patient-professional communication, their experiences should be taken into account by policy makers, health care organizations, and information technology enterprises when developing patient portals. In addition, more training regarding web-based patient-professional communication and patient portals should be provided to health care professionals.